Pigs immunized with Chinese highly pathogenic PRRS virus modified live vaccine are protected from challenge with North American PRRSV strain NADC-20. Issue 30 (9th July 2015) - Galliher-Beckley, Amy; Li, Xiangdong; Bates, John T.; Madera, Rachel; Waters, Andrew; Nietfeld, Jerome; Henningson, Jamie; He, Dongsheng; Feng, Wenhai; Chen, Ruiai; Shi, Jishu
Highlights We found that JXA-1R MLV vaccine can protect pigs from HP-PRRSV challenge in a U.S. setting. We also found that JXA-1R can protect pigs from NA circulating PRRSV NADC-20 challenge. Protection may be due to JXA-1R-induced broadly neutralizing antibodies and enhanced pulmonary IFN-α/β production.